Revised Statutes of the State of Maine 709 (1840), tit. 12, ch. 169, § 16 - (:unkn) unknown (General Publisher, 1821)
Prohibited going armed with any dirk, dagger, sword, pistol, or other offensive and dangerous weapon without reasonable caue to fear asssault on oneself, their family, or property. Violators required to give sureties not exceeding one year.
--
Keywords: GOING ARMED